2016
DOI: 10.1002/jso.24357
|View full text |Cite
|
Sign up to set email alerts
|

Can the ACS-NSQIP surgical risk calculator predict post-operative complications in patients undergoing flap reconstruction following soft tissue sarcoma resection?

Abstract: The ACS-NSQIP universal risk calculator did not maintain its predictive value in patients undergoing flap reconstruction following STS resection. J. Surg. Oncol. 2016;114:570-575. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 25 publications
3
56
0
Order By: Relevance
“…The data collected from this was then used to create a calculator to generate a risk for a patient based on their medical comorbidities and the procedure they are having performed based on the Current Procedural Terminology (CPT) code 21,22 . In addition, this calculator has been highlighted by the Centers for Medicare and Medicaid Services to enhance the preoperative discussion for risk of surgery and provides financial incentives for surgeons to use this calculator 23–25 …”
Section: Introductionmentioning
confidence: 99%
“…The data collected from this was then used to create a calculator to generate a risk for a patient based on their medical comorbidities and the procedure they are having performed based on the Current Procedural Terminology (CPT) code 21,22 . In addition, this calculator has been highlighted by the Centers for Medicare and Medicaid Services to enhance the preoperative discussion for risk of surgery and provides financial incentives for surgeons to use this calculator 23–25 …”
Section: Introductionmentioning
confidence: 99%
“…In a study of 153 patients undergoing fibular free flaps, none of the SRC complication estimates showed statistically significant association with the observed rates of complications . Slump et al came to similar conclusions in a study of 79 myocutaneous free flaps . Additionally, Riley et al showed that the SRC was an inadequate predictor of LOS in patients undergoing any head and neck free flap surgery .…”
Section: Discussionmentioning
confidence: 86%
“…Recently, there has been increasing interest and focus on quality measures and complication rates in medicine. Head and neck free tissue transfer surgery is uniquely positioned because it stands as the gold standard for reconstruction following cancer extirpative surgery but suffers from a high complication rate, with reports ranging from 30% to 60% . Because complications are linked to undesirable sequelae such as increased cost and LOS, obtaining a detailed prediction of a patient's risk for postoperative complications is a vital part of the decision‐making process and should drive patient education and surgical candidacy discussions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations